2018
DOI: 10.1016/j.jbusres.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Country-of-origin image (COI) as a country-specific advantage (CSA): Scale development and validation of COI as a resource within the firm perspective

Abstract: The study discusses the country-of-origin-image (COI) as a country-specificadvantage (CSA) for internationalised firms. We developed and validated a scale to measure the importance of the incorporation of the COI as a resource in a firm's international strategy, the COI-CSA. Several psychometric procedures were adopted. We analysed data gathered from two case studies, validation procedures with experts and researchers, and three data sets from executives working in internationalised firms. The results validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 88 publications
(161 reference statements)
4
67
0
Order By: Relevance
“…This may imply that country-oforigin information becomes more accessible and relevant for wellknown brands in consumer perceptions of brand globalness, compared with lesser-known brands from the same country. These findings are in general agreement with extant literature on country-of-origin effects (Han, 1989: Jaffe & Nebenzahl, 2006Sharma, 2011;Barbarossa et al, 2018;Suter et al, 2018) and may also imply that country-of-origin effects can also occur in consumer perceptions of brand globalness.…”
Section: Theoretical Implicationssupporting
confidence: 90%
See 2 more Smart Citations
“…This may imply that country-oforigin information becomes more accessible and relevant for wellknown brands in consumer perceptions of brand globalness, compared with lesser-known brands from the same country. These findings are in general agreement with extant literature on country-of-origin effects (Han, 1989: Jaffe & Nebenzahl, 2006Sharma, 2011;Barbarossa et al, 2018;Suter et al, 2018) and may also imply that country-of-origin effects can also occur in consumer perceptions of brand globalness.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…Past research suggests that country of origin affects consumer evaluations of quality for foreign brands (Barbarossa et al, 2018;Halkias et al, 2016;Suter et al, 2018), in spite of criticisms that country of origin is no longer an important quality signal due to global branding and multinational production (Samiee, 2011;Usunier, 2006), Consumers activate a preexisting image of a country's products in their brand evaluations (Roth & Diamantopoulos, 2009). Studies have indicated that the mere presence of country-specific stimuli can automatically activate country-specific images, even when consumers do not intend to use country of origin in their brand evaluations (Herz & Diamantopoulos, 2013;Liu & Johnson, 2005).…”
Section: Country-of-origin and Brand Globalness Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The country of origin may be played to become a competitive advantage (Cuervo‐Cazurra & Un, ) and a scale may be even be developed to turn the image of a country into an advantage (Suter, Borini, Floriani, da Silva, & Polo, ). However, negative country of origin images are frequently grounded on overarching impressions, as weak institutions and weak market reputations, that entrepreneurs may find hard to change individually (Fiaschi, Giuliani, & Nieri, ).…”
Section: Could a Negative Country Of Origin Image Become A Self‐fulfimentioning
confidence: 99%
“…Their value proposition cannot be as easily appreciated abroad as coffee, when in 50‐kg bags, or as Brazilian made planes, when flying. This is why it is so hard to turn Brazil's country image, so focused on extraction activities (Suter et al, ) into a competitive advantage when selling products of the mind. To sell black boxes for a fair price one needs salespersons more sure of their worth of their national identity.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%